1993
DOI: 10.1007/bf00019938
|View full text |Cite
|
Sign up to set email alerts
|

Structure and evolution of a highly repetitive DNA sequence from Brassica napus

Abstract: A Hind III family of highly repetitive DNA sequences, canrep (canola repeat), was cloned from the nuclear DNA of canola (Brassica napus cv. Westar). The basic units of this family of repeats consists of 176 bp and are arranged in clusters of tandem direct repeats. Each canrep repeat is composed of three related subrepeats of ca. 60 bp. Each subrepeat contains two inverted repeats of about 23 bp and another unrelated sequence of about 12 bp. Based on the internal structure, a possible scheme for the evolution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…oleracea DNA in Southern blot hybridisations under high stringency conditions and when we compared this sequence with pBo1.6 similarity was found in only a small region (55 bp). No similarity was found between pBo1.6 and previous described repetitive sequences found in Brassica genomes (Benslimane et al, 1986;Reddy et al, 1989;Harbinder and Lakshmikumaran, 1990;Lakshmikumaran and Ranade, 1990;Gupta et al, 1990Gupta et al, , 1992Iwabuchi et al, 1991;Xia et al, 1993Xia et al, , 1994Harrison and Heslop-Harrison, 1995;Kapila et al, 1996b;Lim et al, 2005;Hong et al, 2006). As B .…”
Section: Discussionmentioning
confidence: 59%
“…oleracea DNA in Southern blot hybridisations under high stringency conditions and when we compared this sequence with pBo1.6 similarity was found in only a small region (55 bp). No similarity was found between pBo1.6 and previous described repetitive sequences found in Brassica genomes (Benslimane et al, 1986;Reddy et al, 1989;Harbinder and Lakshmikumaran, 1990;Lakshmikumaran and Ranade, 1990;Gupta et al, 1990Gupta et al, , 1992Iwabuchi et al, 1991;Xia et al, 1993Xia et al, , 1994Harrison and Heslop-Harrison, 1995;Kapila et al, 1996b;Lim et al, 2005;Hong et al, 2006). As B .…”
Section: Discussionmentioning
confidence: 59%
“…In centromere regions of maize (Alfenito and Birchler, 1993;Ananiev et al, 1998), pearl millet (Kamm et al, 1994), rice (Dong et al, 1998), sugarcane (Nagaki et al, 1998), sorghum (Zwick et al, 2000), the Australian daisy Brachycome dichromosomatica (Leach et al, 1995), rape (Xia et al, 1993), and the wild beet Beta procumbens (Gindullis et al, 2001), tandem repeats have been found that differ in sequence but that all have lengths in the range of ‫ف‬ 140 to 180 bp. Particular repeat arrays in cereals have been estimated to be hundreds of kilobases long (Dong et al, 1998;Kaszás and Birchler, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Twelve 2 Charon 4A clones, namely xlel, xle3, xle4, xle6, xle7, xle13, xle21, xle23, xle24, xle25, xle28 and xle29, were chosen for further analysis because they appeared to contain clusters of the canrep sequence that potentially were flanked by other types of DNA. The hybrid DNAs from these clones were digested with Eco RI, and the resultant fragments were subcloned in E. coliJM83r as inserts in the pUC18 and pUC19 [44] or pEMBL18 and pEMB L 19 [ 11 ] plasmids. According to the name of each original clone and the isolation number of each subclone, they were named xle4-7, xle6-14, xle7-2, xle13-11, xle21-2, xle21-16 and xle28-4.…”
Section: Subcloning and Genealogy Of Canrep-containing Dna Segmentsmentioning
confidence: 99%